2006
DOI: 10.1093/brain/awl297
|View full text |Cite
|
Sign up to set email alerts
|

Delayed ischaemic neurological deficits after subarachnoid haemorrhage are associated with clusters of spreading depolarizations

Abstract: Progressive ischaemic damage in animals is associated with spreading mass depolarizations of neurons and astrocytes, detected as spreading negative slow voltage variations. Speculation on whether spreading depolarizations occur in human ischaemic stroke has continued for the past 60 years. Therefore, we performed a prospective multicentre study assessing incidence and timing of spreading depolarizations and delayed ischaemic neurological deficit (DIND) in patients with major subarachnoid haemorrhage (SAH) requ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
549
6
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 517 publications
(583 citation statements)
references
References 56 publications
23
549
6
5
Order By: Relevance
“…In SAH, CSD provided excellent detection of subsequent delayed ischemic neurological deficits (positive predictive value, 86%; negative predictive value, 100%). The events of neurological decline were closely time-linked to CSD, providing biologic plausibility for their role as more than an epiphenomenon [80]. Invasive measures of brain tissue oxygenation showed that waves of CSD following SAH resulted in significant stress on the balance of brain oxygen supply and demand, causing waves of brain tissue hypoxia followed by rebound hyperoxia.…”
Section: Cortical Spreading Depressionmentioning
confidence: 99%
“…In SAH, CSD provided excellent detection of subsequent delayed ischemic neurological deficits (positive predictive value, 86%; negative predictive value, 100%). The events of neurological decline were closely time-linked to CSD, providing biologic plausibility for their role as more than an epiphenomenon [80]. Invasive measures of brain tissue oxygenation showed that waves of CSD following SAH resulted in significant stress on the balance of brain oxygen supply and demand, causing waves of brain tissue hypoxia followed by rebound hyperoxia.…”
Section: Cortical Spreading Depressionmentioning
confidence: 99%
“…An entirely different scenario may apply in the human brain acutely injured for example by ischemic stroke, brain trauma, or subarachnoid or intracerebral hemorrhage (ICH) (Hansen and Lauritzen, 1984;Strong et al, 2002;Fabricius et al, 2006;Dreier et al, 2006;Dohmen et al, 2008). This has been studied recently in patients who underwent neurosurgery including craniotomy because of their acute brain condition, by using cortical electrode strips similar to the technology applied in epilepsy surgery.…”
Section: Introductionmentioning
confidence: 99%
“…7-9 Clusters of SD impose particularly severe energy demands on the injured brain. [15][16][17][18] Clinical microdialysis enables monitoring of the local metabolic status of brain tissue in patients with TBI. [18][19][20][21][22][23][24] Boutelle and coworkers developed a rapid sampling microdialysis (rsMD) system that monitors SD-associated glucose transients with 30-s temporal resolution.…”
mentioning
confidence: 99%